e-Water Transportation Management System - Anizal, Faris Ariedwan; Ab. Aziz, Mohamad Firdaus (Applied Information Technology And Computer Science, 2021)
Abstract: Water transportation management was created to accommodate the transportation of the water to the customer especially in rural access which have limited access to the clean water supply. The existing system of transportation water seems to be inconvenience which customer needs to take a queue to get the water at the available water station. Thus, a solution must be proposed to ensure the effectiveness in the transportation of fresh and clean water directly to the customer. The main objectives of the proposed system are to design, develop and test e – Water Transportation Management System and the scopes of the project will be involving the customer, transporter, and administrator as the user for this proposed system. The tools in developing the system are Xampp, MySQL and PHP as the programming language. The methodology used in the project is Waterfall Development Model. As a conclusion, e – Water Management System will increase the effectiveness in transporting the fresh and clean water directly to the customer efficiently through the transporter through this Web-based system. Keywords: Water transportation, customer, Web-based system.